Peningkatan Pemahaman Cara Berwudhu Melalui Penerapan Metode Demonstrasi dan Simulasi - Afidah, Mu'rifatul; Witasari, Rinesti; Fathoni, Khoirul (Civiliza Publishing, 2024)
This study aims to improve the understanding of how to perform ablution among students of Madin Al Hidayah Sukorejo Village through the application of demonstration and simulation methods with the Asset-Based Community Development (ABCD) approach. This study involved 10 elementary school students who were guided directly during the learning process by KPM students and assisted by Madin Al Hidayah teachers. Through the stages of observation, discussion, practice and documentation. The results of the study showed that the application of demonstration and simulation methods with the ABCD approach significantly improved students' understanding of the correct way to perform ablution. The learning process became more interactive and contextual, because it involved active participation from students, teachers, and KPM students. The conclusion of this study indicates that the demonstration and simulation method, with the ABCD approach, can be an effective strategy in improving students' understanding of worship procedures, especially ablution.